Hypothetical Protein from Aspergillus niger contains Chromate Reductase Motifs - Sallau, A. B.; Fiona Henriquez,; Sani Ibrahim,; Andrew Jonathan Nok; H M Inuwa,; Craig W. Roberts (UMYU Journal of Microbiology Research)
Chromate reductase is an enzyme that converts toxic and carcinogenic Cr6+ to non-carcinogenic and less soluble Cr3+. A hypothetical protein (ref.XP-001388504.1) from Aspergillus niger has been identified as chromate reductase using bioinformatics techniques. The techniques involved Clustal W alignment and Basic Local Alignment Search Tool (BLAST). Using Clustal W alignment the motifs VTPEYN and LKNAID motifs were identified to be common among the different chromate reductase homologues aligned. The same motifs reappeared when the hypothetical protein was aligned with other chromate reductase homologues. The BLAST search was able to also identify VTPEYN and LKNAID motifs on the A. niger genome indicating the likelihood of the hypothetical protein being chromate reductase. The homologue was recovered as putative chromate reductase gene encoded by an open reading frame of 2227 bp nucleotide sequence. These findings clearly demonstrate the hypothetical protein is likely to be chromate reductase.